Stereotypical Processing of Emotional Faces: Perceptual and Decisional Components - Fitousi, Daniel (Frontiers in Psychology, 2021)
People tend to associate anger with male faces and happiness or surprise with female faces. This angry-men-happy-women bias has been ascribed to either top-down (e.g., well-learned stereotypes) or bottom-up (e.g., shared morphological cues) processes. The dissociation between these two theoretical alternatives has proved challenging. The current effort set to tackle this challenge by harnessing two complementary metatheoretical approaches to dimensional interaction: Garner’s logic of inferring informational structure (Garner, 1974b) and General Recognition Theory – a multidimensional extension of signal detection theory (GRT, Ashby & Townsend, 1986). Conjoint application of these two rigorous methodologies afforded us to: (a) uncover the internal representation that generate the angry-men-happy-women phenomenon, (b) disentangle varieties of perceptual (bottom-up) and decisional (top-down) sources of interaction, and (c) relate operational and theoretical meanings of dimensional independence. The results show that the angry-men-happy-women bias is generated by both perceptual and decisional biases. These outcomes document the involvement of both bottom-up (e.g., shared morphological structures) and top-down (stereotypes) factors in social perception.